1987
DOI: 10.1007/bf00215527
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the size and number of secretion granules in the rat exocrine pancreas induced by feeding or stimulation in vitro

Abstract: The size, number and volume per cell of secretion granules in rat exocrine pancreas have been measured using stereological techniques. The changes which occur as a result of feeding starved animals (90 min) or stimulating lobular fragments in vitro with carbachol are documented. In fasted animals mean acinar cell volume was estimated as 1670 micron 3 and the cells contained an average of around 450 secretion granules with a corrected mean diameter of 0.70 micron. They occupied around 7% of cell volume. After f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…It should be noted that the size of the pancreas zymogen granules is variable and depends on physiological and developmental factors. For instance, in starved animals the diameter of zymogen granules is increased by about 20 to 30% (6,18). We observed a similar increase when comparing starved and fed mice.…”
Section: Discussionsupporting
confidence: 81%
“…It should be noted that the size of the pancreas zymogen granules is variable and depends on physiological and developmental factors. For instance, in starved animals the diameter of zymogen granules is increased by about 20 to 30% (6,18). We observed a similar increase when comparing starved and fed mice.…”
Section: Discussionsupporting
confidence: 81%
“…The K increase may reflect heightened protein synthesis [ 15], Acinar cell volume was 1.790 pm3 in the control group and 2,457 pm3 in the experimental group. The control value compares well with the earlier reports of 1,740 urn3 [32], 1,670 pm3 [33] and 1,464-1,804 pm ' for peri-insular cells [34],…”
Section: Discussionsupporting
confidence: 79%
“…Morphological studies had also reported the same effect after feeding (Ermak & Rothman 1981, Aughsteen & Cope 1987) and pharmacological stimulation (Beaudoin et al 1984). Ermak & Rothman (1981) suggested that these changes reflected the loss of protein across the membrane, as proposed in the equilibrium hypothesis (Rothman 1975).…”
Section: Discussionmentioning
confidence: 79%